Happy family. - Poh, Ruth Xiu Jing. (2013)
Identity has always been the core of human existence as it shapes our values, ideas and habits. It is also the central tenet of social organization. In Singapore, the State has categorized identities into groups such as race, religion and socio-economical status. However, there are many problems and inaccuracies with this top-down categorization. Identity is always in a state of flux and it is being negotiated and renegotiated with the state. But there are many problems with this process of negotiation due to the lack of platforms that allow individuals to openly and actively participate in the development and negotiation of multiple identities with possibilities for these to evolve in different contexts in our fast changing urban environment. Identity should not be controlled by the state because the citizens own it collectively and therefore should have a major and active role in its shaping. The aims of this project are to firstly, use visual communication as an interactive tool to explore and investigate how Singaporeans construct identity, and secondly to open up ways of narrating, imagining and articulating identity in Singapore.